Perkembangan Penelitian Wajib Pajak dengan Omset Tertentu : A Systematic Literature Review - Lutfia, Citra; Puspita Sari, Rika; Alafi Hidayatin, Dina; Faisol, Faisol; Rahayu Dewi Zakiyah RF (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2025)
This research is motivated by the imbalance between the important role of MSMEs in making a large contribution to state revenue, or Gross Domestic Product (GDP) with the imbalance of state revenue from the tax sector sourced from MSMEs. MSMEs that are able to contribute 61% of GDP are unable to increase the amount of state revenue in the tax sector. Through this research, it is expected to find results about the current state and trends of research related to taxpayers with a certain turnover or often referred to as MSME Taxpayers, with a time span from 2014 to 2024. The method used in this study is Symantic Literature Review, using secondary data in the form of 20 articles. The results found that in the period 2014-2024, the variable of taxpayer compliance is a variable that is often raised in research, followed by the object of Small Business Taxation. Of the 20 articles used as research data, most used the survey method. In addition, the results found that the topic of tax compliance in MSMEs is worthy of further study because it is still very relevant to future conditions.